God as a fruitful illusion? Ernst Bloch’s „Atheism in Christianity“ - Machoń, Henryk (Hybris, 2014)
Either almighty God or a free man: this is an alternative of atheistic critique of religion. In this context, the aim of the article is to present Ernst Bloch’s (1885–1977) original proposal, concluded in his Atheism in Christianity. Standing for atheistic humanism he finds an inspiration in the Bible, in the classical example of Job’s (undeserved) suffering. Bloch’s original and appealing concept of Marxist revolution is based on hope and the idea of liberation, which are very characteristic of him. This article focuses on such issues of philosophy of religion as the biblical concept of God, the proposal of Job’s radical dilemma of righteous man’s suffering or the significance of eschatology for understanding immutability of God in His essence, who acts in mutable history.